2019
DOI: 10.1136/bjsports-2018-099683
|View full text |Cite
|
Sign up to set email alerts
|

Does adding hip exercises to quadriceps exercises result in superior outcomes in pain, function and quality of life for people with knee osteoarthritis? A systematic review and meta-analysis

Abstract: ObjectivesTo determine, in people with knee osteoarthritis (KOA): i) the effectiveness of adding hip strengthening exercises to quadriceps exercises and ii) the type of hip strengthening exercise with the greatest evidence for improving pain, function and quality of life.DesignSystematic review with meta-analysis.Data sourcesMedline, Embase, Cochrane, CINAHL and SportDiscus databases were searched from inception to January 2018.Eligibility criteria for selecting studiesRandomised controlled trials investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 48 publications
0
35
0
1
Order By: Relevance
“…Since TrPs are not associated with muscle atrophy, more complex mechanisms can be involved in knee OA and post-surgical knee pain. Most trials (n=3, 75%) applied the needling intervention to the knee musculature; a recent meta-analysis reported that the inclusion of exercises targeting the hip musculature resulted in greater improvements in pain and function in patients with knee OA [ 55 ]. Another explanation may be that knee OA or post-surgery knee pain can also have a neuropathic mechanism (up to 25% of the patients) [ 56 ], not influenced by the effects of dry needling.…”
Section: Discussionmentioning
confidence: 99%
“…Since TrPs are not associated with muscle atrophy, more complex mechanisms can be involved in knee OA and post-surgical knee pain. Most trials (n=3, 75%) applied the needling intervention to the knee musculature; a recent meta-analysis reported that the inclusion of exercises targeting the hip musculature resulted in greater improvements in pain and function in patients with knee OA [ 55 ]. Another explanation may be that knee OA or post-surgery knee pain can also have a neuropathic mechanism (up to 25% of the patients) [ 56 ], not influenced by the effects of dry needling.…”
Section: Discussionmentioning
confidence: 99%
“…The strength actions shown to be discriminative (on the most affected leg) in another of our case-vs-healthy control studies (28) on the same sample, were evaluated as X 3i (cf. Results, Table 1), but therein we also included hip abduction due to prior proven causal/trial effects (26,85). For choosing the first and second candidate predictors, we also considered a confounding analysis (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few of these studies were rated as high quality according to a recent meta-analysis. 19 More special targeted trials are needed to further confirm the functional benefit of strengthening the hip abductor. This study was thereby designed to determine whether the addition of hip abductor training to conventional quadriceps training could result in better performance, higher self-reported function and more pain relief in Asian women with symptomatic knee osteoarthritis.…”
mentioning
confidence: 99%